“Agora abriuse algunha porta e sae toda para fóra”: the Mimesis of Memory in Galician Novel of the 21st Century - Rivadulla Costa, Diego (Madrygal. Revista de Estudios Gallegos, 2020)
In the last two decades, Galician novels that thematize the recent past of the Spanish Civil War and Francoism have multiplied and specialized, so that the corpus of “memory narrative” already forms a literary subgenre of its own in Galicia. It is our hypothesis that one of the main changes shown by the texts published since 2000 with respect to the previous memorialistic novels is that they are not only realistic representations of traumatic events related to resistance or Francoist repression, for example, but rather the processes of individual and collective remembrance of those events are central topics of the narrative digesis itself. This paper proposes an analysis of the literary representation of memory or “mimesis of memory” in a group of recent Galician novels like Expediente Artieda by Luís Rei Núñez, O exiliado e a primavera by Manuel Veiga or Home sen nome by Suso de Toro.
Keywords: Cultural Memory; Spanish Civil War; Francoism; Galician Narrative; Mimesis of Memory